EVALUATING MSME FINANCING PRACTICES DURING COVID-19: EVIDENCE FROM ISLAMIC BANK ANNUAL REPORTS - Umar, Umar Habibu; Darma , Auwalu Isah (Journal of Central Banking Law and Institutions, 2024)
This study assesses the MSME financing practices of Islamic banks in Bangladesh during the COVID-19 pandemic. The study examines the annual reports of Bangladeshi Islamic banks between 2020 and 2021. This study found Islamic bank financing for cottage, small and medium enterprises (CMSME) through agent banking was effective during the pandemic. Banks also launched various programs, products, and schemes easily accessible to CMSMEs in the country, including special programs supporting women entrepreneurship and CMSMEs in rural areas. Overall, the performance of MSME financing of Islamic banks in the country was impressive and effective measured by the amounts disbursed to CMSMEs, the number of beneficiaries, new branches opened, and employment of bank staff to handle the enterprises’ financial requests over the period. The findings can help the government and regulatory agencies, particularly Bangladesh Bank, during the revision of regulations to enhance CMSME financing by scheduled banks in the country.